Relationship of Education and Long-term Nursing work with the Performance of Nurses in RSU - Nova Rita; Siti Handam Dewi; Vitratul Illahi (Professional Evidence-based Research and Advances in Wellness and Treatment, 2024)
One of the cornerstones of vital health services in the community or medical facility is nursing care. It centers on the delivery of high-quality nursing care, which can be handled by competent, driven professional nurses. Such talents can be influenced by elements that come from the nurses themselves as well as external factors like length of service and education level. Nurse performance is one of the important aspects of quality health care. Good performance from nurses can improve the quality of patient care, efficiency of health services, and patient and family satisfaction. This study employed a cross-sectional research methodology to examine the association between nurses' performance and their duration of service and educational attainment. Because this design enables the researcher to measure these variables at a single moment in time, it was selected. This study focused on every nurse employed by the RSU hospital.  The results of the chi-square test calculation for the variable level of education and nurse performance show a chi-square value of 17,469 with a p value of 0.002. Since the p value is <0.05, it can be concluded that there is a significant relationship between education level and nurse performance. Education Improvement: Use scholarship programmes, tuition support, or flexible study times to encourage nurses to continue their education. Continuous Training: Ongoing training and professional development programmes ensure that nurses have the knowledge and skills relevant to nursing trends. Reward for Experience: Recognise and reward nurses' work experience by providing greater opportunities and responsibilities for professional advancement.